Acetaldehyde production by major oral microbes. (20th April 2015) - Moritani, K; Takeshita, T; Shibata, Y; Ninomiya, T; Kiyohara, Y; Yamashita, Y
<x xml:space="preserve">Abstract</x> Objectives To assess acetaldehyde (ACH) production by bacteria constituting the oral microbiota and the inhibitory effects of sugar alcohols on ACH production. Materials and Methods The predominant bacterial components of the salivary microbiota of 166 orally healthy subjects were determined by barcoded pyrosequencing analysis of the 16S rRNA gene. Bacterial ACH production from ethanol or glucose was measured using gas chromatography. In addition, inhibition by four sugars and five sugar alcohols of ACH production was assayed. Results Forty‐one species from 16 genera were selected as predominant and prevalent bacteria based on the following criteria: identification in ≥95% of the subjects, ≥1% of mean relative abundance or ≥5% of maximum relative abundance. All Neisseria species tested produced conspicuous amounts of ACH from ethanol, as did Rothia mucilaginosa, Streptococcus mitis and Prevotella histicola exhibited the ability to produce ACH. In addition, xylitol and sorbitol inhibited ACH production by Neisseria mucosa by more than 90%. Conclusions The oral microbiota of orally healthy subjects comprises considerable amounts of bacteria possessing the ability to produce ACH, an oral carcinogen. Consumption of sugar alcohols may regulate ACH production by oral microbes.